Active Lower Range of Motion Reduce the Sign and Symptom of Diabetic Neuropathy - Ika Yuni Widyawati; Dewi Irawaty; Luknis Sabri (Universitas Airlangga, 2010)
Introduction: The aimed of this study for the 56 members of PERSADIA Surabaya was to determine the effect of active lower range of motion exercise on the signs and symptoms of diabetic neuropathy in type II Diabetes Mellitus's patients.Method: A quasy experimental pre-post test design with a consecutive sampling technique was used in this study.Result: The results showed that there was a significant differences between control and treatment groups for muscle strength with p value 0.047 but not for tendon reflexes, protective sensation, ankle brachial index and diabetic polyneuropathy complaints.Discussion: It can be concluded that active lower range of motion exercise has an effect on muscle strength in patients with type II of Diabetes Mellitus with microvascular complications.